The mischief of the mistletoe - Willig, Lauren (Willig, Lauren. Pink carnation series., 2010)
Despite her dear friend Jane Austen's warning against teaching, Arabella Dempsey accepts a position at a girls' school in Bath, just before Christmas. She hardly imagines coming face-to-face with French aristocrats and international spies. Reginald "Turnip" Fitzhugh-often mistaken for the elusive spy known as the Pink Carnation-has blundered into danger before. When Turnip and Arabella find their Christmas pudding yielding a cryptic message, they are launched on a Yuletide adventure. Will they find poinsettias-or peril?